Application of novel microwave-assisted vacuum frying to reduce the oil uptake and improve the quality of potato chips. (November 2016) - Su, Ya; Zhang, Min; Zhang, Weiming; Adhikari, Benu; Yang, Zaixing
Abstract: The objective of this study was to evaluate the ability of microwave-assisted frying (MVF) technology to reduce the oil uptake and improve quality attributes of fried potato chips. Potato chips were produced using MVF and vacuum frying (VF) technologies and the oil uptake, residual moisture content, microstructure, texture (crispness) and color attributes of chips were compared. The effects of microwave power density (12, 16 and 20 W/g), frying temperature (100, 110 and 120 °C) and vacuum degree (0.065, 0.075 and 0.085 MPa) in MVF were evaluated. Results showed that the oil uptake in MVF samples was significantly lower than VF samples, decreased from 39.14 to 29.35 g oil/100 g dry solid. The moisture evaporation rates were accelerated and the MVF produced crispier chips with better natural color. Higher microwave power densities resulted in faster water evaporation rates and lower breaking force. Higher frying temperature led to faster water evaporation, lower oil content and faster color change. Higher vacuum degree bring about faster water evaporation, lower oil content and less color change. Observation of microstructure showed that the cellular structure and integrity of cell wall in chips was better preserved by MVF. Highlights: Microwave-assisted frying (MVF) makes lower oil uptake in potato chips than VF. MVF improves the texture and color attributes of fried potato chips. The microwave power density and frying temperature affect the quality of products. The cellular structure and integrity of cell wall in chips was better preserved by MVF.